Serum vitamin B12 and folic acid status in Autism spectrum disorder children - Mahruba, Syeda Nusrat; Begum, Shelina; Shahjadi, Shorifa; Afroz, Sharmin; Siddiqi, Umme Raihan; Parvin, Jobaida (Journal of Bangladesh Society of Physiologist, 2020)
Background: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder. The etiology of ASD involves gene-environmental interaction. Vitamin B12 and folic acid have important roles as methyl donor in many biosynthetic pathways, protein synthesis and formation of myelin sheath throughout the central nervous system. Therefore, deficiency of vitamin B12 and folic acid may act as environmental risk factor for ASD. Objective: To evaluate serum vitamin B12 and folic acid levels in ASD children. Methods: This cross-sectional study was conducted in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka, from 2018 to 2019. Total 100 children 3-10 years of age were enrolled for this study.Among them fifty (50) diagnosed children with ASD were included in the study group. Fifty (50) healthy children constituted the control group. ASD children were selected from the Parent’s Forum for autistic children. No children were included receiving any vitamin supplementation or had acute illness. For this study, serum level of vitamin B12 and folic acid were measured by automated analyzer.For statistical analysis unpaired “t” test and chi square test were done. Result: The mean values of vitamin B12 and folic acid were significantly lower in ASD children than those of control group (p value <0.05). In addition 4% ASD children had vitamin B12 deficiency. Conclusion: Low serum vitamin B12 and folic acid was associated with ASD. J Bangladesh Soc Physiol. 2019, December; 14(2): 43-47